Integrating Natural Deep Eutectic Solvents into Nanostructured Lipid Carriers: An Industrial Look - Luísa Schuh; Luane Almeida Salgado; Tathyana Benetis Piau; Ariane Pandolfo Silveira; Caio Leal; Luís Felipe Romera; Marina Arantes Radicchi; Mac-Kedson Medeiros Salviano Santos; Leila Falcao; Cesar Koppe Grisolia; Eliana Fortes Gris; Luis Alexandre Muehlmann; et al. (MDPI AG, 2024)
The industries are searching for greener alternatives for their productions due to the rising concern about the environment and creation of waste and by-products without industrial utility for that specific line of products. This investigation describes the development of two stable nanostructured lipid carriers (NLCs): one is the formulation of a standard NLC, and the other one is the same NLC formulation associated with a natural deep eutectic solvent (NaDES). The research presents the formulation paths of the NLCs through completeness, which encompass dynamic light scattering (DLS), zeta potential tests, and pH. Transmission electron microscopy (TEM) and confocal microscopy were performed to clarify the morphology. Cytotoxicity tests with zebrafish were realized, and the results are complementary to the in vitro outcomes reached with fibroblast L132 tests by the MTT technique and the zymography test. Infrared spectroscopy and X-ray diffractometry tests elucidated the link between the physicochemical characteristics of the formulation and its behavior and properties. Different cooling techniques were explored to prove the tailorable properties of the NLCs for any industrial applications. In conclusion, the compiled results show the successful formulation of new nanocarriers based on a sustainable, eco-friendly, and highly tailorable technology, which presents low cytotoxic potential.